Modeled Respiratory Tract Deposition of Aerosolized Oil Diluents Used in Δ9-THC-Based Electronic Cigarette Liquid Products - Ranpara, Anand; Stefaniak, Aleksandr B.; Williams, Kenneth; Fernandez, Elizabeth; LeBouf, Ryan F. (Frontiers in Public Health, 2021)
Electronic cigarette, or vaping, products (EVP) heat liquids (“e-liquids”) that contain substances (licit or illicit) and deliver aerosolized particles into the lungs. Commercially available oils such as Vitamin-E-acetate (VEA), Vitamin E oil, coconut, and medium chain triglycerides (MCT) were often the constituents of e-liquids associated with an e-cigarette, or vaping, product use-associated lung injury (EVALI). The objective of this study was to evaluate the mass-based physical characteristics of the aerosolized e-liquids prepared using these oil diluents. These characteristics were particle size distributions for modeling regional respiratory deposition and puff-based total aerosol mass for estimating the number of particles delivered to the respiratory tract. Four types of e-liquids were prepared by adding terpenes to oil diluents individually: VEA, Vitamin E oil, coconut oil, and MCT. A smoking machine was used to aerosolize each e-liquid at a predetermined puff topography (volume of 55 ml for 3 s with 30-s intervals between puffs). A cascade impactor was used to collect the size-segregated aerosol for calculating the mass median aerodynamic diameter (MMAD) and geometric standard deviation (GSD). The respiratory deposition of EVP aerosols on inhalation was estimated using the Multiple-Path Particle Dosimetry model. From these results, the exhaled fraction of EVP aerosols was calculated as a surrogate of secondhand exposure potential. The MMAD of VEA (0.61 μm) was statistically different compared to MCT (0.38 μm) and coconut oil (0.47 μm) but not to Vitamin E oil (0.58 μm); p < 0.05. Wider aerosol size distribution was observed for VEA (GSD 2.35) and MCT (GSD 2.08) compared with coconut oil (GSD 1.53) and Vitamin E oil (GSD 1.55). Irrespective of the statistical differences between MMADs, dosimetry modeling resulted in the similar regional and lobular deposition of particles for all e-liquids in the respiratory tract. The highest ( 0.08 or more) fractional deposition was predicted in the pulmonary region, which is consistent as the site of injury among EVALI cases. Secondhand exposure calculations indicated that a substantial amount of EVP aerosols could be exhaled, which has potential implications for bystanders. The number of EVALI cases has declined with the removal of VEA; however, further research is required to investigate the commonly available commercial ingredients used in e-liquid preparations.